Evaluation on the rheological and mechanical properties of concrete incorporating eggshell with tire powder - Rokiah, Othman; Beng, Wei Chong; Putra Jaya, Ramadhansyah; Mohd Rosli, Mohd Hasan; Mohd Mustafa Al Bakri, Abdullah; Mohd Haziman, Wan Ibrahim (Elsevier Ltd, 2021)
The construction industry is the largest consumer of raw materials which are under the risk of exhaustion and depletion in the near future, which has prompted the usage of waste materials for the conservation of resource and as a solution for waste management. Two wastes that are widely produced but often inefficiently disposed are eggshell and waste tire. Hence, this paper aims to evaluate the rheological and mechanical properties of concrete incorporating eggshell and waste tire rubber using Response Surface Methodology (RSM). Concrete with eggshell as cement replacement and waste tire rubber as sand replacement was prepared with an interval of 5% up to 15% replacement of both materials. Rheological properties of concrete were accessed using slump cone test while mechanical properties were studied through compressive strength and flexural strength test. Result showed that eggshell replacement has a minor effect on concrete slump while tire rubber reduces workability considerably. Result also showed that concrete mechanical strength was optimum at 5% and 10% eggshell replacement, while tire rubber reduced mechanical strength with percentage of replacement. Non-destructive tests indicated that concrete has excellent quality but excessive tire replacement beyond 10% compromised structural integrity of concrete. Overall, RSM models were able to model the properties of concrete with high accuracy and minimal deviation.